Does age affect the response of pelvis and spine to simulated leg length discrepancies? A rasterstereographic pilot study - Wild, Michael; Kuehlmann, Britta; Stauffenberg, Anna; Jungbluth, Pascal; Hakimi, Mohssen; Rapp, Walter; Betsch, Marcel (European Spine Journal, 2014)
Purpose: The purpose of this study was to investigate age differences in the response of the spine and pelvis to simulated leg length inequalities (LLIs). Methods: A total of 107 subjects, separated into three age groups (group 1: 20-39 years, group 2: 40-59 years, group 3: >60 years), were used to evaluate for any age effects in the response to LLIs. LLIs of +10, +20, and +30 mm were simulated with a simulation platform on both sides, and the respective changes of pelvic position (pelvic obliquity, pelvic torsion) and spinal posture (lateral deviation, surface rotation, kyphotic, and lordotic angles) were measured with a rasterstereographic system. Results: In all three age groups an increase in LLI led to significant changes in the pelvic position as measured by the parameters of pelvic obliquity and torsion. No significant differences in the response of the pelvis to the LLIs were found between the age groups. In all age groups an increase in surface rotation and lateral deviation of the spine with increasing LLIs was found. However, none of these parameters responded significantly different between the three age groups. Conclusions: Under static conditions, LLIs lead to significant changes of the pelvic position and spinal posture. Despite all known age-related changes, no significant differences of the measured pelvic and spinal parameters in elderly patients as a response to the simulated LLIs occurred. © 2014 Springer-Verlag.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Age-dependent; Leg length inequalities; Pelvis; Rasterstereography; Spine